Astrometria, efemérides e ocultações estelares de satélites irregulares e corpos do sistema solar exterior - Gomes Júnior, Altair Ramos (2018)
The study of outer Solar System bodies like trans-Neptunian objects (TNOs), Centaurs and Irregular Satellites (relatively unaltered remnants from the early Solar System) helps us to understand the formation and evolution of the Solar System. Only a few spacecrafts were sent to explore these regions and much of the still relatively small knowledge about their characteristics were acquired from ground-based observations and from space telescopes. Nowadays, it’s accepted that TNOs and Centaurs have been formed at a inner region of the Solar System and that part of this population was captured by the giant planets during the planetary migration, originating their irregular satellites. What is left to know is how and when. In order to help answering these questions it is necessary to characterize their physical parameters. One of the best techniques to characterize size, shape, density, atmosphere, rings, etc, it is the stellar occultation technique. This work presents the analysis of two stellar occultations by Ceres, the work on stellar occultations by TNOs and Centaurs developed by our group in collaboration with foreign researchers, the astrometry, ephemeris production and stellar occultation prediction by irregular satellites, the first stellar occultation by an irregular satellite (Phoebe) ever observed, the astrometry of the Neptune- Triton system and the prediction work of the recent successfully stellar occultation by Triton at October 05, 2017. During an 1-year stay at the Observatoire de Paris during my PhD, I developed, under the supervision of Dr. Valéry Lainey, an independent code of numerical integration of orbits of planetary satellites intended to ephemeris generation. This code allows our group to be more independent, because nowadays this is developed only by french and american groups. All of the phases of a stellar occultation were studied: observations of objects, astrometry, numerical modeling of orbits, stellar occultation predictions, prediction updates, observations of occultation, photometric analysis of light curves and fit of the immersion and emersion instants to the shape of objects, including 3D numerical models available in the literature. All these steps prepare us for the big campaign of stellar occultations by irregular satellites of Saturn predicted for 2018 and of Jupiter predicted for 2019-2020, when these planets will cross the apparent Galatic plane on sky.